Firm-to-firm relationships and the pass-through of shocks: Theory and evidence - Sebastian Heise (Federal Reserve Bank of New York, 2019)
Economists have long suspected that firm-to-firm relationships might lower the responsiveness of prices to shocks due to the use of fixed-price contracts. Using transaction-level U.S. import data, I show that the pass-through of exchange rate shocks in fact rises as a relationship grows older. Based on novel stylized facts about a relationship's life cycle, I develop a model of relationship dynamics in which a buyer-seller pair accumulates relationship capital to lower production costs under limited commitment. The structurally estimated model generates countercyclical markups and countercyclical pass-through of shocks through variation in the economy's rate of relationship creation, which falls in recessions.
Keywords: E30; E32; F14; L14; 330; prices; exchange rate; supply chain; trade relationships